Ecosocialism and Emerging Accounting Theories - Osorio, Jorge Humberto Ramirez; H. , Monica Maria Aristizabal; Osorio, Diego Fernando Serna (Journal of Posthumanism, 2025)
The modes of production that have been developed to meet human needs have impacted the planet and the ecosystems that form it in different ways. They are two modes of production that have opposite positions; the first is socialism which has permanently and rigorously criticized capitalism as the production model that contributes the most to the deterioration of the planet and human beings; which confers greater value on the monetary economy, develops to increase profits. The socialist position that is opposed to capitalist forms of production, in the relationship with natural resources, humanity and the planet, influences the emergence of other currents and ideologies that, despite having somewhat different visions, converge on the same thing, the conservation of ecosystems; doctrines, which aim to change the production model, to one that gives greater value to the moderate and responsible use of non-renewable resources, proposing strategies to meet the needs of society that are sustainable and in balance with life on the planet.